Views of the Seventh-day Adventist Church on Offerings and Tithing - Arthur Sitompul; Janes Sinaga; Juita Lusiana Sinambela (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to provide a deep and Biblical understanding of Tithing and offerings. Give the right view according to the Torah. This research method is a qualitative method of literature study. Managing finances well as a form of God's blessing, is an important thing that should be in the life of a believer. Tithing is an important aspect of giving that cannot be ignored in the life of a believer. This tithe is applied to His people not because God is lacking, so God expects a tithe from each of His people. The church must realize that everything belongs to God. Tithing is not a gift to get God's blessing, but because God has blessed it first, believers respond by giving tithes.